Limitations of PLX3397 as a microglial investigational tool: peripheral and off-target effects dictate the response to inflammation - Claeys, Wouter; Verhaege, Daan; Van Imschoot, Griet; Van Wonterghem, Elien; Van Acker, Lore; Amelinck, Laura; De Ponti, Federico F.; Scott, Charlotte; Geerts, Anja; Van Steenkiste, Christophe; Van Hoecke, Lien; Vandenbroucke, Roosmarijn E. (Frontiers in Immunology, 2023)
Microglia, the resident macrophages of the central nervous system (CNS), play a critical role in CNS homeostasis and neuroinflammation. Pexidartinib (PLX3397), a colony-stimulating factor 1 (CSF1) receptor inhibitor, is widely used to deplete microglia, offering flexible options for both long-term depletion and highly versatile depletion-repopulation cycles. However, the potential impact of PLX3397 on peripheral (immune) cells remains controversial. Until now, the microglia-specificity of this type of compounds has not been thoroughly evaluated, particularly in the context of peripherally derived neuroinflammation. Our study addresses this gap by examining the effects of PLX3397 on immune cells in the brain, liver, circulation and bone marrow, both in homeostasis and systemic inflammation models. Intriguingly, we demonstrate that PLX3397 treatment not only influences the levels of tissue-resident macrophages, but also affects circulating and bone marrow immune cells beyond the mononuclear phagocyte system (MPS). These alterations in peripheral immune cells disrupt the response to systemic inflammation, consequently impacting the phenotype irrespective of microglial depletion. Furthermore, we observed that a lower dose of PLX3397, which does not deplete microglia, demonstrates similar (non-)MPS effects, both in the periphery and the brain, but fails to fully replicate the peripheral alterations seen in the higher doses, questioning lower doses as a ‘peripheral control’ strategy. Overall, our data highlight the need for caution when interpreting studies employing this compound, as it may not be suitable for specific investigation of microglial function in the presence of systemic inflammation.